2010
DOI: 10.1111/j.1423-0410.2009.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticomplementary activity of IVIG concentrates - important assay parameters and impact of IgG polymers

Abstract: Background and Objectives A high concentration of large size polymers in intravenous immunoglobulin preparations was always correlated with high anticomplementary activity (ACA). In former days, high ACA was also linked to adverse reactions in patients. The goal of this study was to scrutinize critical parameters of the ACA assay and the influence of different polymer variants of IgG on the complement consumption. Materials and MethodsCritical reagents as the complement and the preparation of erythrocytes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…com/news/home/20100924005668/en/Update-Withdrawal Product-Recall---octagams-octagams5). These events can be caused by trace impurities in the preparation or by unpredicted changes to the Ig molecule that can occur during the production process [59,60,63]. These unexpected side reactions occurred recently, and no analytical data were published yet in order to give a hint about possible impurities that caused these serious accidents.…”
Section: Intravenous Igg Concentratesmentioning
confidence: 93%
See 1 more Smart Citation
“…com/news/home/20100924005668/en/Update-Withdrawal Product-Recall---octagams-octagams5). These events can be caused by trace impurities in the preparation or by unpredicted changes to the Ig molecule that can occur during the production process [59,60,63]. These unexpected side reactions occurred recently, and no analytical data were published yet in order to give a hint about possible impurities that caused these serious accidents.…”
Section: Intravenous Igg Concentratesmentioning
confidence: 93%
“…Triton X100 and tri n-butylphosphate) [58]. Buchacher et al [59] have demonstrated that the anticomplementary activity of IVIG concentrates is caused by a high concentration of large polymers in some products. They also demonstrated that conditions under which polymers are formed (e.g.…”
Section: Intravenous Igg Concentratesmentioning
confidence: 98%
“…18 The effect was termed 'anti-complement activty' (ACA) and later the absence of such activity became a release criterion for IVIG. 38 The method how to get a 'close to native' immunoglobulin G concentrate suitable for intravenous application is an example of serendipity in research. Barandun and Isliker were doing in vitro experiments with pepsin treatment of "standard" IgG concentrate.…”
Section: Nabs In Immunoglobulin Concentrates: Historical Aspect Of Thmentioning
confidence: 99%
“…Àíòèêîìïëåìåíòàðíàÿ àêòèâíîñòü (ÀÊÀ) èíôóçèîííûõ ïðåïàðàòîâ Ig ÷åëîâåêà ÿâëÿåòñÿ îäíèì èç êëþ-÷åâûõ ïîêàçàòåëåé ñïåöèôè÷åñêîé áåçîïàñíîñòè èììóíîãëîáóëèíîòåðàïèè. ÀÊÀ îáóñëîâëåíà ïðèñóòñòâèåì â íèõ àãðåãèðîâàííûõ è/èëè ïîâðåaeäåííûõ ïðè ôðàêöèîíèðîâàíèè ìîëåêóë Ig, íà Fc-ó÷àñòêå êîòîðûõ ïðîèñõîäèò ñïîíòàííàÿ àêòèâàöèÿ êîìïëåìåíòà â îòñóòñòâèå êîìïëåêñîâ àíòèãåí -àíòèòåëî [1,2]. Ñîãëàñíî ðåêîìåíäàöèÿì ýêñïåðòîâ ÂÎÇ, âñå ñåðèè èíôóçèîííûõ ïðåïàðàòîâ Ig ÷åëîâåêà ïîäëåaeàò îáÿçàòåëüíîìó èñïûòàíèþ íà ÀÊÀ.…”
unclassified
“…Ñîãëàñíî ðåêîìåíäàöèÿì ýêñïåðòîâ ÂÎÇ, âñå ñåðèè èíôóçèîííûõ ïðåïàðàòîâ Ig ÷åëîâåêà ïîäëåaeàò îáÿçàòåëüíîìó èñïûòàíèþ íà ÀÊÀ. Ìåòîäèêà îïðåäåëåíèÿ ÀÊÀ ñîïðÿaeåíà ñ ðÿäîì êðèòè÷åñêèõ ïàðàìåòðîâ [1], ñâÿçàííûõ ñ èñïîëüçîâàíèåì áèîëîãè÷åñêèõ ðåàãåíòîâ, òàêèõ êàê êîìïëåìåíò ìîðñêèõ ñâèíîê, ýðèòðîöèòû áàðàíà è ãåìîëèòè÷åñêàÿ ñûâîðîòêà, âàðèàáåëüíîñòü êîòîðûõ îáóñëàâëèâàåò íåîáõîäèìîñòü èñïîëüçîâàíèÿ ñòàíäàðòíîãî îáðàçöà (ÑÎ), ïîëîaeèòåëüíûé è îòðèöàòåëüíûé êîíòðîëè êîòîðîãî ïîäòâåðaeäàþò äîñòîâåðíîñòü ïîëó÷àåìûõ ðåçóëüòàòîâ â ðàçëè÷íûõ äèàïàçîíàõ çíà÷åíèé ÀÊÀ. Îïòèìèçèðîâàííàÿ ìåòîäèêà îïðåäåëåíèÿ ÀÊÀ [3,4] ïðåäóñìàòðèâàåò èñïîëüçîâàíèå aeåëàòèí-ñîëåâîãî ðàñòâîðà, êàê àëüòåðíàòèâàaeåëàòèí-áàðáèòàëîâîãî áóôåðíîãî ðàñòâîðà, ïðåäóñìîòðåííîãî ñòàíäàðòèçîâàííîé ìåòîäèêîé Åâðîïåéñêîé ôàðìàêîïåè (ÅÔ) [5].…”
unclassified